Rapid Fermentable Substance Modulates Interactions between Ruminal Commensals and Toll-Like Receptors in Promotion of Immune Tolerance of Goat Rumen - Shen, Hong; Lu, Zhongyan; Chen, Zhan; Wu, Yufeng; Shen, Zanming (Frontiers in Microbiology, 2016)
Whether dietary non-fiber carbohydrate (NFC), a rapid fermentable substance, affects immune homeostasis of rumen through the modulation of interactions of ruminal microbiota and epithelial toll-like receptors (TLRs) remains unclear. A combination of 16S rRNA amplicon sequencing and quantitative PCRs was applied to study the synergetic responses of ruminal microbiota and epithelial TLRs to the dietary NFC switch from 15% to 31% in the goat model. The results showed that the 35% NFC diet caused the radical increases on the richness and diversity of rumen microbiota. The phylum Verrucomicrobia was most significantly expanded, whereas opportunistic pathogens, namely Rikenella, Anaeroplasma, and Olsenella, were significantly decreased. In rumen epithelium, the significantly increased expressions of TLR1, 6, 10 were associated with the significantly decreased expressions of pro-inflammatory cytokines interleukin-1beta (IL-1ß), IL-6, and anti-inflammatory cytokine IL-10. Constrained correlation analysis indicated that the increased abundance of commensal bacteria in Verrucomicrobia subdivision 5 contributed to the upregulation of TLR10 expression. Finally, the significantly increased concentrations of rumen SCFAs, coupled with the significantly upregulated expressions of epithelial genes related to short chain fatty acid (SCFA) absorption were observed in goats fed with 31% NFC diet. Thus, the NFC-induced expansion of rumen microbiota promoted epithelium tolerance by enhancement of the intensity of TLR10 signaling. The newly established equilibrium benefited to the transport of ruminal energy substances into the blood.